2013
DOI: 10.1080/09650792.2013.854173
|View full text |Cite
|
Sign up to set email alerts
|

Action research to improve collaboration among Student Support Services teams

Abstract: This study explores action research as a professional development strategy to improve interprofessional collaboration in a school division team focused on supporting students with a variety of learning and behavioural needs. Occupational therapists, speech and language pathologists, a psychologist, and a social worker worked together to learn more about each other's scopes of practice and overcome challenges to collaboration. Action research provided an effective medium for competency development, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The purpose of the present study was to examine the effects of a one-day interprofessional learning experience designed to promote increased understanding of the various roles of school professionals and provide an opportunity for students to participate in interprofessional collaboration within a simulated school-based context. As mentioned previously, researchers have indicated that effective collaborative techniques must be developed, taught, and practiced in order to build competency (Anderson, 2013;Dobbs-Oates & Watcher Morris, 2016;Hong & Shaffer, 2015;Salm, 2014).…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of the present study was to examine the effects of a one-day interprofessional learning experience designed to promote increased understanding of the various roles of school professionals and provide an opportunity for students to participate in interprofessional collaboration within a simulated school-based context. As mentioned previously, researchers have indicated that effective collaborative techniques must be developed, taught, and practiced in order to build competency (Anderson, 2013;Dobbs-Oates & Watcher Morris, 2016;Hong & Shaffer, 2015;Salm, 2014).…”
Section: Current Studymentioning
confidence: 99%
“…Studies have shown that effective collaborative techniques must be developed, taught, and practiced in order to build competency and produce effective outcomes (Anderson, 2013;Dobbs-Oates & Watcher Morris, 2016;Hong & Shaffer, 2015;Salm, 2014). Based on the research, which indicated that shared decision-making yields better results for students and teachers, professional organizations have acknowledged interprofessional collaboration as an essential component in professional training at higher education institutions (Arredondo, Shealy, Neale, & Winfrey, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we have succeeded in making a firm commitment to joint collaboration as junior researchers in order to consolidate an inter-university community of practice in the future, with the objective of making contributions based on the transformation of our own practice. Action research is an effective professional development strategy for collaboration and (Salm 2013;Zehetmeier 2015). Initially we have been able to critically review the process together with other external networks, as a result of participation in wider contexts, in our attempt to increase collaboration and dissemination of knowledge.…”
Section: Findings and Limitationsmentioning
confidence: 99%
“…Recent research highlights the practical transformative potential of action research, insofar as participants have become creators of multimedia educational resources (Crotty, 2012(Crotty, , 2014, active creators of school resources (McLaughlin and Ayubayeva, 2015), have implemented new support structures to assist parents and teachers (Salm, 2014) and have improved and changed their teaching strategies as a result of engaging in the action research process (Kayaoglu, 2015). These changes in practice came about through individual and group reflections, which highlights the key role of reflection in transforming thought into practice.…”
Section: The Transformative Potential Of Armentioning
confidence: 99%
“…It was clear at the end of Cycle One that I had not achieved my aim to motivate my students to communicate spontaneously in the target language. Watching the video evidence of how students collaborated to develop a script for the multimedia files, my validation group suggested that students were quite hesitant and subdued, and that little spontaneous communication had occurred …This is particularly evident from the footage of collaboration on the audio script …This made me aware of the need to reflect on the process and how I might approach a second cycle (post-primary teacher, 2012, p. 48) Cycle Two: At the end of cycle two, the post-primary teacher commented on how she had created a much more communicate environment:…”
Section: Collaboration Performance and Peer Validationmentioning
confidence: 99%